Tecnomatix Plant Simulation Modeling and Programming by Means of Examples - Bangsow, Steffen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book systematically introduces readers to the development of simulation models as well as the implementation and evaluation of simulation experiments with Tecnomatix Plant Simulation. Intended for all Plant Simulation users whose work involves complex tasks, it also offers an easy start for newcomers. Particular attention has been paid to introducing the simulation flow language SimTalk and its use in various aspects of simulation. In over 200 examples, the author demonstrates how to combine the blocks for simulation models and how to employ SimTalk in complex control and analysis tasks. The content ranges from a description of the basic functions of the material flow blocks to more advanced topics such as the implementation of database-supported warehouse control by using the SQLite interface, and the exchange of data using XML, ActiveX, COM or DDE. .
Basics -- SimTalk and Dialogs -- Modeling of Production Processes -- Information Flow, Controls -- Working with random values -- Simulation of transport processes -- Simulation of Robots and Handling Equipment -- Warehousing and Procurement -- Simulation of Workers -- The Fluids Library -- 2D and 3D Visualization -- Integrate Energy Consumption and Costs -- Statistics -- Data Exchange and Interfaces.
Keywords: Computational intelligence; Artificial intelligence; Production management; Industrial engineering; Production engineering; Engineering$1 (BData processing.s; Engineering mathematics; Computational Intelligence; Artificial Intelligence; Operations Management; Industrial and Production Engineering; Data Engineering; Engineering Mathematics